A comparative study to evaluate the performance of the short passing and receiving skills in handball players The youth of Erbil and Sulaymaniyah clubs: (Raparin Journal of Humanities (RJH), 2024)
There is no doubt that the handball game is one of the sports that develops the level of skillful performance of its players at the level of Iraqi clubs, and the Erbil and Sulaymaniyah clubs are among the clubs that are interested in the game of handball and who have been within the elite clubs for several years in Iraq due to the presence of a broad base of players at levels Young, junior and advanced, In order to identify the most important differences in the level of performance of the handling and handball skills of the young players in the two clubs, the researcher used the descriptive approach using the causal comparison method, and in which special tests were determined to evaluate the performance of the short passing skills and receiving   handball of the players.As for the research sample, it consisted of youth players from Erbil and Sulaymaniyah clubs, and their number was (20) players, with (10) players for each club, and the researcher relied on a set of devices and tools for the purpose of conducting tests and obtaining raw grades after conducting the tests approved by the gentlemen. Experts and specialists.After conducting the statistical process by means of the (spss) program, the results showed a convergence of the level in my tests (compatibility and speed of passing, pass-through) between the youth players of Erbil and Sulaymaniyah clubs, and the presence of significant differences in the test (prolonged throwing of the ball) between the players of the youth of the two clubs, and in favor of the youth club players Erbil, and the researchers recommended the necessity of conducting an assessment of the performance level of all basic handball skills, and the necessity of evaluating the performance level of basic handball skills for all youth club players in the region and comparing them with the players of advanced youth clubs in Iraq.